2005
DOI: 10.1016/j.ejcts.2004.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Does the extent of lymph node dissection influence outcome in patients with stage I non-small-cell lung cancer?

Abstract: Importance of lymph node dissection affects patients outcome, while it does not enhance the operative mortality. A minimum of 10 lymph nodes assessed, and two mediastinal stations sampled are suggested as possible pragmatic markers of the quality of lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
87
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 22 publications
(38 reference statements)
9
87
0
Order By: Relevance
“…It is noteworthy that, even for patients who underwent complete mediastinal lymphadenectomy, the median survival of those who had an RUL tumor location (not reached) was better numerically than for those who had an RLL tumor location (50.7 months). 23 Thus, better staging of the mediastinal lymph nodes, especially Level 8 and 9 lymph nodes, by endoscopic, ultrasound-guided fine-needle aspiration; integrated computed tomography-positron emission tomography fusion scan; video-assisted thoracoscopy 24 ; or more complete mediastinal lymphadenectomy [25][26][27][28] will provide better management for nonupper lobe tumors in patients with early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, even for patients who underwent complete mediastinal lymphadenectomy, the median survival of those who had an RUL tumor location (not reached) was better numerically than for those who had an RLL tumor location (50.7 months). 23 Thus, better staging of the mediastinal lymph nodes, especially Level 8 and 9 lymph nodes, by endoscopic, ultrasound-guided fine-needle aspiration; integrated computed tomography-positron emission tomography fusion scan; video-assisted thoracoscopy 24 ; or more complete mediastinal lymphadenectomy [25][26][27][28] will provide better management for nonupper lobe tumors in patients with early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Izbicki (10) and Graham (38) argued that LND should be routinely operated for resectable NSCLC. On one hand, whether LND would increase postoperative morbidity associated with complications is not clear (10,36) and the influence on outcome such as overall survival and diseasefree survival remains controversial (5,8,17,33,34). On the other hand, the reported benefit that SLND can shorten the entire medical period along with its validity, reliability and applicability are still not very clear.…”
Section: Discussionmentioning
confidence: 92%
“…Among all the lung cancer-therapeutic methods, surgery plays a pivotal role, especially in the early-stage nonsmall cell lung cancer (NSCLC). Nowadays, the standard surgical treatment of early-stage NSCLC is lobectomy with systematic lymph node dissection (LND) as recommended by the guidelines (3,4), which capable of providing accurate staging (5,6), detecting occult metastasis (7) and improving survival (5,8,9). However, randomized trials have not demonstrated that LND has more survival benefit than sampling (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…The proponents of MLNR assert that it improves the staging accuracy by increasing LN harvest and enhances the identification of occult N2 disease (3,4). With respect to therapeutic effect, MLNR-according to its proponentsdecrease recurrence and increase survival by removing the occult N2 disease.…”
mentioning
confidence: 99%